PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM (Studi Empiris pada Perusahaan Sub Sektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2023): Fakultas Ekonomi dan Bisnis, Universitas Budi Luhur - Sari, Ayu Sekar; Laksmiwati, Mia (PT. Media Edutama Nusantara, 2024)
ABSTRACT The aim of this study is to identificate how firm size, liquidity, profitability, and leverage impact the value of its shares. The businesses operating in the telecommunications subsector that are listed on the Indonesia Stock Exchange for the 2019–2023 timeframe make up the population that is used. Through the use of purposive sampling and secondary data, this study produced a population of 22 firms, of which 15 were listed on the Indonesia Stock Exchange in the the telecommunications subsector between 2019 and 2023. Multiple linear regression analysis, done with the Statistical Program for Social Science (SPSS) version 22, is the analysis approach used. The study's conclusions show that while liquidity and leverage have little bearing on the value of shares, profitability and firm size do.